Universal design for learning: Review and recommendations for EFL instruction - Timpe-Laughlin, Veronika; Laughlin, Michael K. (Inklusiver Englischunterricht. Impulse zur Unterrichtsentwicklung aus fachdidaktischer und sonderpädagogischer Perspektive, 2018)
Keywords: dept.hms

Assistive Technology: What Physical Educators Need to Know - Laughlin, Michael K., Murata ,Nathan M., Gonnelli ,Michele; and Larranaga, John (Journal of Physical Education, Recreation & Dance, 2018)
Assistive technology supplements and supports the learning of students with disabilities in school and at home. Thanks to federal mandates, students with disabilities receive consideration for assistive technology devices and services — the tools and supports needed to achieve determined learning outcomes. Assistive technology devices and services operate as a process, ensuring students with disabilities receive optimal access to learning across all educational settings and subject areas. This article provides physical educators with a working knowledge of the assistive technology process along with recommendations for supporting their students with disabilities.
Keywords: dept.hms